The mindful coach seven roles for facilitating leader development - Silsbee, Douglas K. (San Francisco Jossey-Bass, 2010)
Written for executive coaches, teachers, and other development professionals, the book explores the seven roles or Voices that coaches assume while working with a client. The Voices are: Master, Partner, Investigator, Reflector, Teacher, Guide and Contractor. Silsbee illuminates the dynamic relationship between these roles, and integrates them in an intelligent roadmap for any coaching conversation. This book offers a helpful resource for internal and external executive coaches as well as leader coaches, consultants, trainers, teachers, and facilitators.
Includes bibliographical references and index.
Keywords: Executive coaching